NILAI KUAT TEKAN GULA AREN - Rambu Ririnsia Harra Hau; Mahardika Prasetya Aji; Sulhadi Sulhadi; Salvo Kahumbu Hau; Soleman Dappa Talu (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
One potential area that have encountered in Indonesian society is brown sugar. There are various types of sugar including coconout sugar, palm sugar, ants sugar and others. Another interesting thing is examined in this study relates to the mechanical properties of palm sugar that is the compressive strength of the palm sugar. Palm sugar is made from sugar palm sap heating on volume of 600ml with a variation of the time is 26 minutes, 27 minutes, 28 minutes, 29 minutes and 30 minutes. The mechanical properties studied were compressive strength of palm sugar. These parameters were measured to determine the maximum size of an acceptable burden the palm sugar. The compressive strength of the palm sugar palm juice on the heating time 30 minutes, namely: 0.115218MPa. From the research results obtained showing a variable effect on the mechanical properties of palm sugar because the longer the heating time, the greater compressive strength. Palm sugar compressive strength of the observed increasing with time is lengthened.Keywords: palm concentrate, palm sugar, compressive strength, the heating time.